Exchange Rate Regimes and Economic Growth: A study from 1974-2019 - Hanif, Saad (2020)
The dissertation focuses upon the impact of exchange rate regimes on the economic growth. The research obtains data from 1974-2019 for 182 countries and applies the K-Means Cluster Analysis using the methodology by Levy-Yeyati and Sturzenegger (2003) to build the de facto exchange rate regimes. The de-facto regimes classifications are based upon the volatility of reserves, exchange rate volatility and volatility of exchange rate changes. Once the de facto regimes are formed, they are compared with Levy-Yeyati and Sturzenegger (2003), Ilzetzki, Reinhart and Rogoff (2019) and Shambaugh (2019). The results of the comparison show around 70% similarities with the other classifications when the unclassified regimes are cancelled out. After the comparison, the growth regression is performed which finds out that the intermediate exchange rate regimes perform better than floating exchange rate regimes in non-industrial countries. The dissertation finds a positive and significant relationship of real economic growth with investment to GDP ratio, openness to trade and changes in terms of trade. Also, the study finds a negative relationship between the economic growth and factors related to population.